Potential Fluorescent Pseudomonad Cas Isolate that Growed in Various Formulas to Produce IAA - Nola Nurdianata; Linda Advinda (Universitas Negeri Padang, 2020)
The purpose of this research was to determine the potential of fluorescent pseudomonad with Cas isolates grown in various formulas to produce Indole Asetic Acid (IAA). This experiment was conducted from June to July 2020, at the Plant Physiology Laboratory of FMIPA, UNP. In this research, IAA detection was carried out by qualitative and quantitative analysis. The research was use descriptive method with fluorescent pseudomonad isolate Cas and treatment consisting of M1 (molasses 10 g/L+ ZA 5 g/L), M2 (molasses 10 g/L+ ZA 10 g/L), M3 (molasses 5 g/L+ ZA 5 g/L), M4 (molasses 5 g/L+ ZA 10 g/L), and M5 (NB 8 g/L). The results showed that the fluorescent pseudomonad of Cas isolate was able to produce IAA. This can be seen in the pink color produced after addition of Salkowsky's reagent and incubation for 12 hours in a dark room. Then, the fluorescent pseudomonad of Cas isolate grown in the M1 formula had the highest IAA concentration of 37.295 ppm, while the lowest IAA concentration was in the fluorescent pseudomonad isolate Cas formula M3 with an IAA concentration of 2.897 ppm.